Analisis Kinerja Alarm Kebakaran Untuk Keselamatan Diatas Kapal - Pinto Kurniawan; Hariyono Hariyono; Faris Nofandi (Politeknik Ilmu Pelayaran Semarang, 2020)
This study aims to determine the causes or factors that can trigger or lead to false alarms, ways to reduce them, determine the design of the alarm system that is applied, and determine the factors so that the fire system can operate optimally on board the ship. The type of research that the author presents is a descriptive type of research with a quantitative approach. Data retrieval was obtained from distributing questionnaires, interviews, and observations of locations and related crew at MV with the data obtained during the Sailing Practice. Ocean Makmur. Research location on the MV. Ocean Makmur. The results showed the cause of the false alarm on the MV. Ocean Makmur, it can be seen that the lack of input or voltage that is less than 20VDC, as well as the infrequent Routine Test (per-unit), and the lack of awareness of the crew itself is the cause of the false alarm. We should anticipate this with our care at work and awareness in our activities.